Resurrecting the brother of Jesus the James Ossuary controversy and the quest for religious relics - Byrne, Ryan.; McNary-Zak, Bernadette (Chapel Hill : University of North Carolina Press, 2009)
This collection of essays explores the circumstances of an archaeological hoax in which a box of skeletal remains was passed off as belonging to James, the brother of Jesus. Contributors discuss the role of media sensationalism, the use and misuse of religion, and the responsibilities of scholars as public interpreters of discoveries with religious significance.
Introduction / Ryan Byrne & Bernadette McNary-Zak -- Archaeological context and controversy : the bones of James unpacked / Byron R. McCane -- The brother of Jesus in Toronto / Thomas S. Bremer -- Finding true religion in the James Ossuary : the conundrum of relics in faith narratives / Bernadette McNary-Zak -- Christian artifacts in documentary film : the case of the James Ossuary / Milton Moreland -- Anatomy of a cargo cult : virginity, relic envy, and hallowed boxes / Ryan Byrne -- Overcoming the James Ossuary and the legacy of biblical archaeology / Jonathan L. Reed -- Epilogue : objects, faith, and archaeoporn / Ryan Byrne & Bernadette McNary-Zak.
Includes bibliographical references and index.
Description based on print version record.
Keywords: James, -- Brother of the Lord, Saint; James Ossuary; Protestant churches -- Doctrines; RELIGION / Biblical Studies / New Testament; Electronic books